The impact of teaching materials on instructional design and teacher development - Lola Garay Abad; John Hattie (Frontiers in Education)
IntroductionTeaching materials are more than just classroom tools — they shape how teachers teach and how they grow professionally. While widely used, their impact across different stages of a teacher’s career has received limited attention. This study explores how different types of materials support both instructional design and professional development, revealing their evolving role across a teacher’s journey.MethodsWe conducted a large-scale survey (n = 2,585) of German-speaking educators, all active users of an online educational platform (eduki). The survey included Likert-scale and open-ended items on material usage, instructional impact, professional growth, and classroom confidence. We analyzed the results using factor analysis and MANOVA to identify patterns and differences across career stages.ResultsFindings show that instructional impact is highest among trainees (mean = 3.55), while the influence on professional growth increases with experience, peaking among very experienced teachers (mean = 3.91). Teacher-created materials were rated as most useful (90.1%), and teachers reported high autonomy (94.1%) in selecting and adapting materials — a factor closely tied to increased classroom confidence. Two strongly correlated factors emerged from the analysis: “Instructional Effectiveness” and “Improve Me as a Teacher.”DiscussionRather than plateauing over time, professional development remains vibrant — and even deepens — with experience. Teaching materials play a key role not only in early-career structure but also in later-career reflection and refinement. Empowering teachers to select and adapt resources appears to strengthen both instructional design and long-term growth, challenging traditional linear models of teacher development.